Nasal High Flow in Room Air for Hypoxemic Bronchiolitis Infants - Franklin, Donna; Babl, Franz E.; Gibbons, Kristen; Pham, Trang M. T.; Hasan, Nadia; Schlapbach, Luregn J.; Oakley, Ed; Craig, Simon; Furyk, Jeremy; Neutze, Jocelyn; Moloney, Susan; Gavranich, John; et al. (Frontiers in Pediatrics, 2019)
Background. Bronchiolitis is the most common reason for hospital admission in infants, with one third requiring oxygen therapy due to hypoxemia. It is unknown what proportion of hypoxemic infants with bronchiolitis can be managed with nasal high-flow in room air and their resulting outcomes. Objectives and Settings. To assess the effect of nasal high-flow in room air in a subgroup of infants with bronchiolitis allocated to high-flow therapy in a recent multicentre randomized controlled trial. Patients and Interventions. Infants allocated to the high-flow arm of the trial were initially treated with room air high-flow if saturations were ≥85%. Subsequently, if oxygen saturations did not increase to ≥92%, oxygen was added and FiO2 was titrated to increase the oxygen saturations. In this planned sub-study, infants treated during their entire hospital stay with high-flow room air only were compared to infants receiving either standard-oxygen or high-flow with oxygen. Baseline characteristics, hospital length of stay and length of oxygen therapy were compared. Findings. In the per protocol analysis 64 (10%) of 630 infants commenced on high-flow room air remained in room air only during the entire stay in hospital. These infants on high-flow room air were on average older and presented with moderate hypoxemia at presentation to hospital. Their length of respiratory support and length of stay was also significantly shorter. No pre-enrolment factors could be identified in a multivariable analysis. Conclusions. In a small sub-group of hypoxemic infants with bronchiolitis hypoxemia can be reversed with the application of high-flow in room air only.